KUAT LENTUR BALOK BETON TAMPANG PERSEGI DENGAN TULANGAN BAMBU WULUNG - , YUDIA PRATIDINA, Prof. Ir. Iman Satyarno, M.E., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Utilization of bamboo as reinforcement have often done, considering the price of steel reinforcement is increasingly expensive and difficult to obtain, so the use of bamboo as reinforcement is likely to be done, because bamboo has several advantages, namely high tension, and easily obtained with a relatively cheap price. However, bamboo also has a weakness, namely the high nature of expand shrink, hygroscopic and low elasticity modulus. The aim of this study was to determine the collapse pattern of the beam, flexural capacity, ductility, and the stiffness of the beam and the influence of wire bond distance of flexural capacity. The research is an effort to utilize bamboo as reinforcement so it can be used for the community home building. It becomes important to be studied and researched further, in order to solve the weaknesses, so that could be better to be used as reinforcement. This research uses bamboo wulung aged about 2-3 years old to be reinforced and then assembled and bonded using an iron wire 2.5 mm in diameter with a variation of the bond distance of 2.5 cm (BB1), 5.0 cm (BB2) and 7.5 cm (BB3). As a waterproof layer used varnish applied to the entire surface of the bamboo reinforcement and paint on both ends. While the sliding reinforcement using 6 mm in diameter plain steel, and cast beams using cement mortar. The making of mortar uses a weight ratio, namely 1:1.5 with fas value of 0.5 and obtained an average compressive strength amounted to 79,01 MPa. The dimension of the beam is 150 mm x 250 mm x 2500 mm. To know the strain that occurs in bamboo and concrete reinforcement, strain gauge mounted on the reinforcement and concrete in each beam, it is placed at mid-span. The test specimens were performed by giving static load at two points in the third span load placed on the loading frame, with joint support roller to obtain pure bending. The parameter sought in this study is the load deflection, strain of bamboo and concrete reinforcement that occur. Then the test results are compared with the theoretical analysis based on SNI 03-2847-2002 and Response-2000 program. The results of testing specimens of the flexural capacity in bamboo beams BB1, BB2, and BB3 in order were 76 kN, 70 kN and 58.8 kN. By comparing the beam flexural capacity of BB1 and BB2 to BB3, they increased by 29.25 % and 19.04 %. The comparison of experiment with theoretical flexural capacity based SNI of 97.61% (BB1), 89.90% (BB2) and 75.52% (BB3) and Response-2000 amounted to 99.51% (BB1), 91.65% (BB2) and 76.98% (BB3). Flexural stiffness BB1, BB2, and BB3 for initial experimental results in a row stiffnes is 4352.94 N / mm, 8571.42 N / mm and 19444.44 N/mm, an increase of BB3 successively for BB1 and BB2 346.69% and 96.91%. When viewed from the crack pattern and variety of the collapse, all beams crack and have flexural collapse caused the failure of bonding. From the acquisition of flexural capacity it is known that the highest flexural capacity of beam is BB1 which has the tightest variation of wire bond distance of 2.5 cm, therefore concluded that the tighter of the bonding wire can increase the flexural capacity.